Structural diversity in a series of metal-organic frameworks (MOFs) composed of divalent transition metals, 4,4 `-bipyridine and a flexible carboxylic acid - Pachfule, Pradip; Panda, Tamas; Dey, Chandan; Banerjee, Rahul (Crystengcomm, 2010)
A series of flexible metal-organic frameworks (MOFs) have been successfully synthesized under hydrothermal condition using 1,3-adamantanediacetic acid (C(14)H(20)O(4), H(2)ADA) as a flexible dicarboxylate building block, 4,4'-bipyridine and transition metal ions [Cd(II), Zn(II), and Mn(II)] as metal centers in DMF and aqueous media. These MOFs formulated as [Cd(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Cd-ADA-1), [Mn(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Mn-ADA-1), Zn(ADA)(4,4'-bipy)(0.5) (Zn-ADA-1), and [Mn(HADA)(2)(4,4'-bipy)(H(2)O)(2)] (Mn-ADA-2) (ADA = 1,3-adamantanediacetate, 4,4'-bipy = 4,4'-bipyridine and DMF = N,N'-dimethyl formamide) display interesting 1D, 2D and 3D structural features depending on the solvent of synthesis. All these MOFs were structurally determined by single-crystal X-ray diffraction. The coordination modes of this ligand are discussed and in addition, thermal stability and hydrogen (H(2)) and carbon-dioxide (CO(2)) adsorption properties of Cd-ADA-1, Mn-ADA-1 and Zn-ADA-1 are also presented. Hydrogen sorption at 77 K and up to 1 atm is found to be 0.42, 0.72 and 1.36 wt% without saturation for Zn-ADA-1, Mn-ADA-1 and Cd-ADA-1 samples.